DIAGNOSIS AND TREATMENT OF MALE INFERTILITY - Silva, J. (2015)
Objective: To determine the current status of male infertility in a general hospital. Design: Descriptive, retrospective study. Material and Methods: We reviewed 371 charts of male patients attended at Arzobispo Loayza Hospital Infertility Service in a 4 - year period. Inclusion criteria were male infertility diagnosis with pathological results in two or more spermatograms and/or ejaculatory sexual dysfunction. Results: We found 79 cases of male infertility, incidence 21,3%. Average age at diagnosis was 35, 9 years, average time of infertility 4 years, 64,8% with primary infertility. Most frequent diagnosis were infection of accessory sexual glands (38%), abnormal seminal plasma (16,5%), azoospermia (15,2%), idiopathic astenozoospermia (12, 7%). Most frequent germ found was hemolytic Streptococcus alpha (50%). 22,8% of the couples conceived mostly with antibiotics use, intrauterine insemination with homologous semen or without treatment. Conclusions: Incidence of male infertility at Arzobispo Loayza Hospital in 4 years was 21,3%. In 87,3% of cases infertility coexists in both members of the couple. Most frequent male infertility diagnosis was accessory sexual glands infection.